(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Contribution Analyst of Water Henna Flower Farming Branch to Total Farming Income in Subak Pama, Tua Village, Marga District, Tabanan. Water henna ﬂower (Impatiens balsamina L.) is a member of the Balsaminaceae family, this plant is widely used as an ornamental plant and medicinal plant. Water henna plant has many variant colour of ﬂowers that are white, red, purple, light purple, pink. The ﬂower shape resembles a small orchid. This study aimed to analyze the income of the water henna ﬂower farming branch in Subak Pama, Tua Village, Marga District and analyze the income contribution of water henna ﬂower farming on the total farming in come in Subak Pama Tua Village, Marga District. The sampling technique used in this study was Non Probability Sampling. The method used in obtaining data in this research is Census method. This study used 30 water henna farmers as research subjects. The average ﬁxed costs incurred in farming water henna ﬂowers for three p lanting seasons amounted to Rp 98.443. Meanwhile, the average variable costs incurred by farmers for three planting periods in water henna ﬂower farming in the amount of Rp 1.094.925. The highest income contribution was obtained from the non-interest water henna ﬂower farming income amounted to Rp 17.594.650 and the income of water henna ﬂower farming was Rp 6.775.385.